The drama review : TDR. (New York University, School of the Arts], 1968)
En el CIICLA está solamente el Volumen 13 Número 4 (T44), Verno 1969 -- Organization mediation / Darko Suvin -- Censorhip / George Papadopoulos -- Media freaking / Abbie Hoffman -- Dramaturgy of radical activity / Lee Braxandall -- Guerrilla theatre from the American playground / Marc Estrin -- Booking the revolution / Saul Gottlieb, Oda Jurges -- Radicalism, secuality, performance / Richard Schechner -- Notes on Paris Street Theatre / Jean-Jaques Lebel -- Three street plays / Theatre de lÉpée de Bois -- Arrbal / The groupuscule of my heart -- A black ritual / Robert Macbeth -- Ceremony of US / Ann Halprin, James T. Burns -- Black revolutionary commercial / Ed Bullins -- Vietnam -- Speech for the theatre / Luigi Pirandello -- Tails / José Ruibal -- The greater sound / Ralph J. Geason -- Peking drama with contemporary themes / Daniel S.P. Yang -- Community dramas of John Arden / Simon Trussler.